2020
DOI: 10.1590/fst.09119
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pasta made of cassava, peach palm and golden linseed flours

Abstract: The possibility of industrially producing new types of pastas based on other types of flour than wheat has raised interest for enabling the use of widely available materials and providing adequate products to persons with celiac disease. A mixture design was developed with the purpose of preparing a gluten-free dry using cassava starch, peach palm meal, and golden linseed while observing the nutritional value added and its technological properties. The pasta underwent assessments of its physicochemical and rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
6
8
1
Order By: Relevance
“…The proximal composition of the BF obtained in the present study was comparable to that described in both the legislation and the literature for flour from other vegetable sources: (i) the moisture content of BF (5.67 g/100 g) was lower than the maximum permitted content for wheat flour (15% w/w) (Brasil, 2005; FDA, 2020); (ii) the protein content of BF (9.15 g/100 g) was similar to that found for wheat (~ 9 g/100 g), corn (4-9 g/100 g), and yellow pea (9.9 g/100 g) (Zhao et al, 2019) flours, and higher than that reported for green banana (3.3 g/100 g) (Flores- Silva et al, 2014) and sweet potato (2.89 g/100 g) (Teye et al, 2018) flours; (iii) the lipid content (0.45 g/100 g) was similar to that reported for green banana (0.5 g/100 g) (Flores- Silva et al, 2014), cassava flour (0.79 g/100 g) (Otondi et al, 2020), and sweet potato (0.76 g/100 g) (Teye et al, 2018) flours, and lower than pupunha (7.89 g/100 g) and flaxseed (21.19 g/100 g) (Sakurai et al, 2020) flours; (iv) the ash content that is related to the mineral content of BF (5.62 g/100 g) was higher than that found for green banana (2.4 g/100 g) (Flores- Silva et al, 2014), manioc and chia (2.59 and 4.98%, respectively) (Otondi et al, 2020), sweet potato (2.19 g/100 g) (Teye et al, 2018), and bean (2.06-3.65 g/100 g) (Rios et al, 2018) flours; (v) the total dietary fiber (21.81 g/100 g) was higher than those reported for sweet potato (3 g/100 g), avocado pear (9.32 g/100 g), and turkey berry (11.13 g/100 g) (Teye et al, 2018) flours; and (vi) the energy value of BF (355.73 kcal) was lower than pumpkin peel (382.54 kcal) (Staichok et al, 2016) and okara (413.92 kcal) (dos Santos et al, 2019) flours.…”
Section: Beet Flour Characterizationsupporting
confidence: 84%
“…The proximal composition of the BF obtained in the present study was comparable to that described in both the legislation and the literature for flour from other vegetable sources: (i) the moisture content of BF (5.67 g/100 g) was lower than the maximum permitted content for wheat flour (15% w/w) (Brasil, 2005; FDA, 2020); (ii) the protein content of BF (9.15 g/100 g) was similar to that found for wheat (~ 9 g/100 g), corn (4-9 g/100 g), and yellow pea (9.9 g/100 g) (Zhao et al, 2019) flours, and higher than that reported for green banana (3.3 g/100 g) (Flores- Silva et al, 2014) and sweet potato (2.89 g/100 g) (Teye et al, 2018) flours; (iii) the lipid content (0.45 g/100 g) was similar to that reported for green banana (0.5 g/100 g) (Flores- Silva et al, 2014), cassava flour (0.79 g/100 g) (Otondi et al, 2020), and sweet potato (0.76 g/100 g) (Teye et al, 2018) flours, and lower than pupunha (7.89 g/100 g) and flaxseed (21.19 g/100 g) (Sakurai et al, 2020) flours; (iv) the ash content that is related to the mineral content of BF (5.62 g/100 g) was higher than that found for green banana (2.4 g/100 g) (Flores- Silva et al, 2014), manioc and chia (2.59 and 4.98%, respectively) (Otondi et al, 2020), sweet potato (2.19 g/100 g) (Teye et al, 2018), and bean (2.06-3.65 g/100 g) (Rios et al, 2018) flours; (v) the total dietary fiber (21.81 g/100 g) was higher than those reported for sweet potato (3 g/100 g), avocado pear (9.32 g/100 g), and turkey berry (11.13 g/100 g) (Teye et al, 2018) flours; and (vi) the energy value of BF (355.73 kcal) was lower than pumpkin peel (382.54 kcal) (Staichok et al, 2016) and okara (413.92 kcal) (dos Santos et al, 2019) flours.…”
Section: Beet Flour Characterizationsupporting
confidence: 84%
“…In addition to direct consumption, peach palm can be used as a raw material for the production of various products, especially in the form of flour (Pires et al, 2019;Valencia et al, 2015), oil (Melhorança & Pereira, 2012), pasta (Oliveira et al, 2006;Sakurai et al, 2019), edible film (Costa et al, 2019), fermented beverage (Andrade et al, 2003), bacterial substrate for amylase production (Oliveira et al, 2007) and functional food products (Rojas-Garbanzo et al, 2012).…”
Section: Physicochemical Compositionmentioning
confidence: 99%
“…However, in a later study, the addition of cassava starch, peach palm flour and gilded linseed allowed the production of well-structured dry pasta. In addition, the mass had a good rate of acceptance and intention of purchase by the tasters (Sakurai et al, 2019). Rosa et al (2016) developed a pre-mix for cake with peach palm (Bactris gasipaes Kunth) flour, free of gluten.…”
Section: Physicochemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample formulations are shown in Table 1. The pasta samples were produced as described by Sakurai, Rodrigues, Pires, and Silva (2019) with some modifications. The cassava flour samples with 0 g, 5 g into 95 g and 10 g into 90 g of fluted pumpkin leaf powder were weighed and mixed manually to achieve a homogenous mixture.…”
Section: Preparation Of Pastamentioning
confidence: 99%